Diálogos con Pablo VI - Guitton, Jean, (Ensayos (Ediciones Encuentro) ;, 2014)
This important, authorized work is a very human document, one that reveals much about Pope Paul VI's own personality and the aura that surrounded him, at the same time that it offers his thoughtful views on pressing concerns of his day.